Drug utilization study of mood stabilizers and antipsychotics drugs among bipolar disorder patients - Lolita Lolita; Johan Ika Meiliana (BIO Web of Conferences)
A key component of SDG 3, which is about good health and wellbeing, is mental illness. The burden of disease and mental illness is a priority for global development. Bipolar is a mental illness that causes unusual changes in mood, energy, physical activity, and concentration. Combinations of mood stabilizers and antipsychotic drugs have significantly altered the long-term prognosis for bipolar patients. This study aims to evaluate the drug utilization of mood stabilizers and antipsychotics in bipolar disorder patients. We conducted a retrospective, descriptive, hospital-based cross-sectional study among bipolar patients attending the psychiatric department at Hospital X, Yogyakarta, Indonesia, from January to May 2017. This study employed two methods to analyse the data: calculating the percentage of rational prescriptions and computing based on the defined daily dose (DDD) per 1000 patient days. In this study, there were 28 respondents between the ages of 26 and 46, with 98 total bipolar cases. 53.6% of participants were female, while 46.4% were male. The rational use of the concurrent administration of mood stabilizers and antipsychotics to patients with bipolar disorder was as follows: 69.39% precise use, 90.82% precise dose, 98.98% precise indication, 76.53% precise patient, and 76.53% precise drug. The result showed that mood stabilizer lithium had the lowest total annual consumption of 2.15 DDD/1000 outpatient visits, and sodium divalproex had the highest total annual consumption of 26.66 DDD/1000 outpatient visits. Risperidone was the antipsychotic with the highest quantity, at 25.92% DDD/1000 outpatient visits, while trifluoperazine had the lowest, at 0.17% DDD/1000 outpatient visits.